Characterization of ZnO:Al deposited by co-sputtering for transparent conductive electrodes - Thuat, Nguyen Tran; Thoa, Bui Bao; Cuc, Than Thi; Hieu, Nguyen Minh; Huong, Hoang Ngoc Lam; Diep, Bui Van; Hieu, Hoang Chi (Communications in Physics, 2015)
Aluminum doped zinc oxide was prepared by magnetron sputtering methods at room temperature using a ZnO ceramic target doped 2%wt by Al2O3. The optical transmittance of the films is higher than 80% in the visible range. A direct bandgap type was reached by controlling deposition conditions; the bandgap value was in the range between 3.2 eV and 4.2 eV. Good electrical and optical properties were obtained for the films deposited by an appropriate co-sputtering of ZnO and Al targets. These films with a resistivity, about 1.3´10-2W.cm, and a transmittance, higher than 80%, can be applicable for transparent conducting electrodes.